The Trinity of Village Transform How Capacity, Participation, and Institutions Shape Development Policy Implementation in Indonesia - Kustiyaman; Triyuni Soemartono; Pandji Sukmana; Gatot Hery Djatmika (Danadyaksa: Post Modern Economy Journal, 2026)
Indonesia's ambitious village governance reform, anchored by Law No. 6 of 2014 and disbursing over IDR 609 trillion in village funds, aims to transform rural communities into self-reliant entities. Yet, significant variation in implementation outcomes persists, even within the same regency. This study investigates how institutional capacity, participatory processes, and collaborative dynamics interact to shape the success of village development policy implementation. Employing a qualitative multi-site case study design, the research examines four villages in Sumedang Regency, West Java, purposively selected to represent the spectrum of development statuses: self-reliant (swasembada), developing (swakarya), and underdeveloped (swadaya). Data were collected through in-depth interviews with 13 informants, participatory observation, and document analysis. The findings reveal that implementation success is not determined by any single factor but by the synergistic interaction of three dimensions, forming a "trinity of village transformation." Villages achieving self-reliant status demonstrate high institutional capacity, quality participatory processes, and robust collaborative dynamics. Trust emerges as a pivotal mediating mechanism, distinguishing virtuous cycles of transformation from vicious cycles of stagnation. Facilitative leadership can compensate for formal capacity limitations. The study concludes by proposing a "Collaborative Implementation Model" that integrates Grindle's (1980) policy implementation framework with Ansell and Gash's (2008) collaborative governance theory, offering both theoretical contributions and practical recommendations for strengthening village development policy.